The Continuity in the Concept: A Concept Analysis of Quality Culture in Complex Adaptive Systems (Journal of Contemporary Educational Policies and Practices, 2023)
In this article we define the concept of quality culture in a complex higher education context. The article aims to start a creative dialogue on the conceptual continuity of the concept of quality culture in the form of a literature review. The concept analysis follows the method of Walker and Avant. We present the method first and thereafter the literature review (&2). The first step of the method is a broad general search on the internet (&2.1.) and a literature review. Numerous articles were selected based on the snowballing strategy and berry picking. The special interest in quality culture in a complex context called for three extra searches. Fifty-eight articles were selected. Two concepts of Quality culture are discovered: quality culture as the creation of shared values and quality culture as ownership of all. There is little literature on quality culture and complexity. In the literature review, little is found about quality culture in a complex context. Only when the definition of the concept of quality culture is known and agreed upon, can we effectively facilitate a quality culture in the complex context of higher education. There is no concept analysis on quality culture available and little research done on the phenomenon of quality culture in a complex context.
Keywords: Quality culture; total quality Management; complexity theory; complex adaptive Systems; shared values; ownership